Curriculum design of joint madrasah system in Islamic education in Singapore - Muhidin, Ihsan; Helmiati; Karim, M. Nazir (Tawazun: Jurnal Pendidikan Islam, 2023)
To accept the increasing modernization and globalization wave, Majelis Ugama Islam Singapura (MUIS) which is responsible for Islamic education in Singapore, introduced the Joint Madrasah System (JMS) to assist madrasahs in improving teachers’ skills, enhancing the curriculum, and optimizing the strengths of each madrasah holistically. The JMS system was implemented in three full-time madrasahs, namely Madrasah Irsyad Zuhri Al-Islamiah, Madrasah Aljunied Al-Islamiah, and Madrasah Al-Arabiah Al-Islamiah. This article aims to describe the curriculum design implemented in the Joint Madrasah Singapore. The research method used in this article is a qualitative method with a combined qualitative approach between library research and field research. Data and information were collected from one of the madrasahs appointed by MUIS as part of JMS, namely Madrasah Irsyad Zuhri Al-Islamiah, in the form of documents, archives, observations, and interviews. The type of research is descriptive qualitative, a form of research that aims to collect and compile data and try to analyze with interpretation or interpretation of these data. Furthermore, in analyzing the data, the author uses two methods, namely the content analysis method and the descriptive analysis method, especially educational analysis. The results show that the curriculum design applied in JMS is an integrative curriculum that eliminates the boundaries between various religious and scientific materials, and presents various subject matter in the form of units or wholes. This was a response from MUIS to improve the quality of the madrasa curriculum to be on par with the national curriculum. Abstrak Untuk mengikuti arus modernisasi dan globalisasi yang begitu cepat, Majelis Ugama Islam Singapore sebagai penanggung jawab pendidikan Islam di Singapura memperkenalkan Joint Madrasah System (JMS) untuk membantu madrasah dalam meningkatkan kemampuan guru, meningkatkan kurikulum, dan mengoptimalkan kekuatan yang ada di setiap madrasah secara holistik. Sistem JMS ini diimplementasikan pada tiga madrasah sepenuh masa, yaitu Madrasah Irsyad Zuhri Al-Islamiah, Madrasah Aljunied Al-Islamiah dan Madrasah Al-Arabiah Al-Islamiah. Artikel ini bertujuan untuk mendeskripsikan desain kurikulum yang diterapkan dalam Joint Madrasah Singapore. Metode penelitian yang digunakan dalam artikel ini adalah metode kualitatif dengan pendekatan kualitatif gabungan antara library research dan field research. Data dan informasi dikumpulkan dari salah satu madrasah yang ditunjuk oleh MUIS sebagai bagian dari JMS, yaitu Madrasah Irsyad Zuhri Al-Islamiah, berupa dokumen, arsip, observasi, dan wawancara. Jenis penelitiannya adalah deskriptif kualitatif, yaitu bentuk penelitian yang bertujuan mengumpulkan dan menyusun data serta mengusahakan dengan analisis secara interpretasi atau penafsiran terhadap data-data tersebut. Selanjutnya dalam menganalisa data, penulis menggunakan dua metode, yaitu metode analisis isi (content analisys) dan metode deskriptif analisis, khususnya analisis kependidikan. Hasilnya didapat bahwa desain kurikulum yang diterapkan dalam JMS adalah kurikulum integratif yang meniadakan batas-batas antara berbagai materi keilmuan agama dan sains, serta menyajikan berbagai bahan pelajaran dalam bentuk unit atau keseluruhan. Hal ini dilakukan sebagai respon MUIS untuk meningkatkan kualitas kurikulum madrasah agar setara dengan kurikulum nasional.